Sexual health of postmenopausal women in North India - Neelam Jain; Reeti Mehra; Poonam Goel; B S Chavan (Wolters Kluwer Medknow Publications, 2019)
Background: Sexual health is the most important aspect of person's well being, self-esteem and quality of life. Sexual pleasure leads to enhanced conjugal relationships and an overall healthy psychological state. There is paucity of data on sexual health of postmenopausal women. Aims and Objectives: To assess the prevalence and determinants of sexual health in postmenopausal women of North India. Materials and Methods: The study was conducted over a period of 18 months, from January 2016 to June 2017. Standard FSFI-6 questionnaire and various socio-demographic factors were used to analyse the sexual health of 110 menopausal women. Results: 80.9% postmenopausal women reported sexual dysfunction (SD). We found more sexual dysfunction in postmenopausal women with increasing age and increasing duration of menopause. Satisfied past sexual experience, joint family structure, low socioeconomic and education status were found to be important determinants of sexual health of postmenopausal females. Parity, substance use and past medical and gynaecological history of participants and various partner's factors like medical disorders, substance use and sexual disorders showed no association with sexual health in postmenopausal females. Conclusion: Sexuality varies with cultural and social differences across the globe. The prevalence of female sexual dysfunction in our study is much higher because Indian women are suppressed, self conscious, inhibited and hesistant to talk about their sexual problems with health care professionals. Also revalidation of the FSFI tool for Indian population is required. Further studies are needed to evaluate the sexual health in postmenopausal women.